Biomarcadores de lesão renal em praticantes de musculação em uso de anabolizantes - Fernandes, Paulo Henrique Palácio Duarte (2017)
To analyze new biomarkers of renal function in bodybuilders who use androgenic anabolic steroids. Method. A cross-sectional study was conducted between April and July 2016 involving individuals who practice weight training in an anabolic group (n = 28) and a non-anabolic group (n = 29). In both groups, a questionnaire containing personal data, training intensity, use of stimulant / anabolic supplements and clinical history was applied. Afterwards, blood and urine samples were collected for analysis of renal injury biomarkers Kidney Injury Molecule-1 (KIM-1) and Monocyte Chemoatactic Protein-1 (MCP-1). Serum levels of creatinine, urea, cystatin, sodium, potassium and chlorine, proteinuria, and glomerular filtration rate were also measured. Results. The participants of the anabolic group were younger (26 ± 5 years, p = 0.006), predominantly male (n = 25, p = 0.004) did more intense training (Borg Scale 7.9 ± 1.7, p = 0.010), they used more caffeine (n = 20, p <0.001), the most frequent ergogenic anabolic steroids (EAA) were testosterone (89.3%) and boldenone (50%). The most commonly reported clinical histories were anxiety (39.3%) and hypertension (17.9%). Regarding the biomarkers, there were significant differences in the anabolic group related to creatinine (1.04 ± 0.17 vs 0.88 ± 0.14 mg / dl, p <0.001), sodium (137 ± 1.4 vs 139 ± 1 , P <0.001), potassium (5.1 ± 0.4 vs 4.6 ± 0.4 mEq / L, p <0.001), serum chlorine (99 ± 1.2 vs 101 ± 1, 6 mEq / L, p <0.001) and MCP-1 levels (50.6 vs. 33 pg / mg-cr, p = 0.039). There was no significant difference regarding KIM-1, glomerular filtration rate, urea and proteinuria. Conclusion. Despite the limitations of the study, the findings of MCP-1 levels point to an incipient renal injury and inflammation in the anabolic group. Further investigation of the chronic use of anabolic steroids is necessary in view of the early detection of renal diseases and correlation with other risk factors.